Correlation between 18F-FDG dosage and SNR on various BMI patient groups tested in NEMA IEC PET phantom - Waeleh, Nazreen; Saripan, M. Iqbal; Musarudin, Marianie; Mashohor, Syamsiah; Ahmad Saad, Fathinul Fikri (Elsevier, 2021)
The present study was conducted to determine quantitatively the correlation between injected radiotracer and signal-to-noise ratio (SNR) based on differences in physiques and stages of cancer. Eight different activities were evaluated with modelled National Electrical Manufacturers Association (NEMA) of the International Electrotechnical Commission (IEC) PET's phantom with nine different tumour-to-background ratio (TBR). The findings suggest that the optimal value of dosage is required for all categories of patients in the early stages of cancer diagnosis.